Dementia care in gerontological social work: emerging issues and challenges in Saudi Arabia - Sultan Ali Shubair (Frontiers Media S.A., 2023)
The issues and challenges in the current state of gerontological social work policy, practice, and education related to dementia care in Saudi Arabia are discussed in this article. The following primary issues were explored: (1) the impact of the biomedical model's global dominance on gerontological social work policy and research for dementia care and health promotion; (2) the position of the older adults in Middle Eastern nations and its connection to the lack of gerontological social work policies, programs, and care services for older adults with dementia and their family caregivers; (3) the effect of the profession of social work's lack of recognition on the potential evolution of gerontological social work practice in dementia care; (4) the state of dementia patients' rights, dementia patients' safety, and dementia patients' rights to self-determination on the gerontological social work support provided for older adults with dementia; (5) the unequal distribution of dementia care resources and gerontological social work; and (6) the social work education programs' inability to supply the market with sufficient number of skilled gerontological social workers and its effect on the advancement of dementia care in gerontological social work practice. Approaches for advancing policy, practice, and education are provided to support the evolution of gerontological social work in dementia care in the region.